Migrant Labor Markets and the Welfare of Rural Households in the Developing World : Evidence from China - de Brauw, Alan; Giles, John (Published by Oxford University Press on behalf of the World Bank, 2019)
Increased ability to migrate from China’s rural villages contributed to significant increases in the consumption per capita of both non-durable and durable goods, and these effects were larger in magnitude for households that were relatively poor before the easing of restrictions to migration. With increased out-migration, poorer households invested more in housing and durable goods than rich households,while richer households invested significantly more in non-agricultural production assets. As migration became easier, increased participation in migrant employment was greater among poorer households on both the extensive and intensive margins, and poorer households reduced labor days in agriculture.